The construction of the Porto School - Fernandes, Eduardo (2019)
The expression ‘School of Porto’ implies an idea of Portuguese Architecture that began in the mid-fifties, in the work of Fernando Távora. In this text, we present an analysis of the Tennis Pavilion of Quinta da Conceição (1957) as an example of Távora’s tectonic shift of the 50s, inspired by the simultaneous influence of Portuguese vernacular construction and of the international debate. This work, along with the others which Távora designed in these years, marks the beginning of a new identity in Portuguese architecture.